A reflective study of supervisors in Higher Education on humanistic strategies of working with 'difficult' students during COVID-19 - Maserole C. Kgari-Masondo; Bernard Chingwanangwana; Aboshioke L. Umejei; Silindile P. Zulu; Balungile C. Zondi; Gabriel G. Darong; Monica Out (Social Sciences and Education Research Review)
This article concentrates on how the migration to digital research supervisory mode affected students in Higher Education (HE) because of COVID-19 globally. Literature on COVID-19 and HE reveals that there have been a lot of hiccups because many students inhabit under-resourced difficult geo-historical and social contexts. These ramifications produce some 'difficult' students who become unproductive in their research as such supervisors required during and beyond the pandemic period are the ones who adopt a humanizing supervision style. The paper tries to close the gaps in the literature on supervisory styles that ignore the role of the geo-historical and social contexts of developing countries by drawing from the qualitative reflections of four supervisors' experiences in HE on how they navigated the context of the 'difficult' students to ensure a success story. The paper's findings are that during COVID-19 and other “challenging times", it is important to use styles of supervision that focus on humanism to make sure that no student is left behind in his/her research. Hence this study proposes the Umuntu Akalahlwa (a person cannot be disposed) supervision style because it emphasizes respect, love, care, hospitality, social justice, and participation as a means of success in research output.